Analysis of the metabolic properties of maintenance hemodialysis patients with glucose-added dialysis based on high performance liquid chromatography quadrupole time-of-flight mass spectrometry - Cui, Li (Dove Medical Press, 2013)
The purpose of this study was to compare the metabolic properties of maintenance hemodialysis patients treated with glucose-containing and glucose-free dialysate using metabonomics. Pre- and post-dialysis serum samples from group G (−) using glucose-free dialysate, and group G (+) using glucose-added dialysate (glucose levels were 5.5 mmol/L) were analyzed and tested with high performance liquid chromatography quadrupole time-of-flight mass spectrometry. Orthogonal signal correction–partial least squares discriminate analysis revealed a significant difference in the post-dialysis metabolic properties between samples from the G (−) and G (+) groups, and concentrations of leucine and dihydroxyprostaglandin F2α were higher in the G (+) group than in the G (−) group. However, markers of reactive lipid mobilization and amino acid release, such as bile acids, aspartate, and valine, were lower in the G (+) group than in the G (−) group. There were no significant differences in excitatory neurotransmitters aspartate and phosphorylated anandamide. Use of liquid chromatography-tandem mass spectrometry metabonomics indicated that using glucose-added dialysate was superior to glucose-free dialysate in the protection of the central nervous system of maintenance hemodialysis patients, but had potential risks in stimulating oxidative stress.